Serological diagnosis of cysticercosis in humans and pigs: status, limitations, and prospects - Hossain, Md. Shahadat; Shabir, Shafqat; Ngwili, Nicholas; Thomas, Lian F.; Falcone, Franco H. (Frontiers in Veterinary Science, 2025)
Cysticercosis is a neglected zoonosis caused by Taenia solium, which involves pigs as intermediate hosts, leading to pig cysticercosis (PCC). Humans are the only definitive hosts, harbouring the mature tapeworm in the small intestines, but they can also act as intermediate hosts upon accidental ingestion of eggs, resulting in human cysticercosis (HCC), called neurocysticercosis (NCC) when the cysts lodge in the central nervous system. Diagnosis of HCC/NCC in humans is based on imaging technologies and serology. The gold standard method for PCC diagnosis is the full carcass dissection and recovery of cysts. However, tongue palpation and meat inspection are the most widely used methods in endemic countries. These methods are specific at the genus level but cannot distinguish mixed infection from other taeniids and are not sufficiently sensitive in pigs with low infection. Available serological tests for human and pig infection are based on parasite-specific immunoglobulin G (IgG). Still, most tests are either cross-reactive with other taeniids or not sensitive enough for single or inactive cysts, particularly for NCC patients. Here, we compare various serological techniques for PCC and NCC published since 2000 and discuss the benefit of IgE-based serodiagnosis as a potential alternative to traditional serology. Considering the diagnostic limitations described above and the need to identify endemic areas to prevent transmission between humans and pigs and monitor control efforts, the development of more sensitive and specific serological tests, followed by a field-applicable point-of-care (POC) test for cysticercosis, is of the utmost importance.